2017
DOI: 10.1002/oby.21854
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in videoconference and in‐person iDiet weight loss programs in worksites and community groups

Abstract: iDiet participants had clinically impactful mean WL. The observed high mean WL in worksites and videoconference-delivered programs broadens options for scalable WL program implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
5
24
0
Order By: Relevance
“…Similarly, lower attrition rates in videoconference vs in-person weight loss classes were demonstrated in a study using another behavioral based weight loss program. 8…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, lower attrition rates in videoconference vs in-person weight loss classes were demonstrated in a study using another behavioral based weight loss program. 8…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of the ongoing Healthy Families Healthy Forces (HF2) randomized controlled trial (trial # NCT02348853). Briefly, the HF2 study compares GLB with a different behavioral weight loss intervention 8 for changes in body weight and cardiometabolic risk factors in adult family members of active duty military personnel or retired military personnel. Participants in the subgroup reported herein were randomized to the GLB arm of the larger trial, and were assigned to either in-person or videoconference groups depending on their date of enrollment and location.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have used videoconference technology to deliver health coaching interventions . In observational analyses of commercial weight loss participants, a 2017 study reported that videoconference participants were more likely to complete the 11‐week programme but not more likely to lose weight . Most recently, a study team reported from two randomized trials (one of 25 and one of 30 adults with obesity) that those randomized to videoconference arms had significantly greater 12‐week weight loss than those randomized to either in‐person or usual care arms .…”
Section: Introductionmentioning
confidence: 99%